1994
DOI: 10.1200/jco.1994.12.9.1789
|View full text |Cite
|
Sign up to set email alerts
|

A decade of breast cancer clinical investigation: results as reported in the Program/Proceedings of the American Society of Clinical Oncology.

Abstract: For breast cancer ASCO abstracts in the past decade, we determined the following: (1) adjuvant trials have not infrequently supported study hypotheses; and (2) advanced-disease trials have consistently failed to identify new approaches with a significant impact on survival. These results suggest that a critical process evaluation of current policy and procedures involved in directing breast cancer research is warranted, especially for strategies in advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…Our results were similar to previous reviews of oncology RCTs [8-10,16,19-21]. Where differences exist these seem to be justified given the differences in the types of trials funded by HTA and NCI.…”
Section: Discussionsupporting
confidence: 89%
“…Our results were similar to previous reviews of oncology RCTs [8-10,16,19-21]. Where differences exist these seem to be justified given the differences in the types of trials funded by HTA and NCI.…”
Section: Discussionsupporting
confidence: 89%
“…Chlebowski and Lillington found that 16% of trials comparing adjuvant therapies for localised breast cancer, but only 2% of trials for advanced breast cancer, favoured experimental treatment 23. We similarly found that trials for advanced solid tumours were less likely than other trials to favour experimental treatment.…”
Section: Discussionsupporting
confidence: 57%
“…An analysis of abstracts on the treatment of breast cancer submitted to a major oncology conference over 10 years showed that, although approximately 16% of randomized trials examining adjuvant chemotherapy showed a significant benefit to the experimental arm, only 2% of trials in advanced-stage disease showed a significant benefit for the experimental arm. 4 In fact, advanced-stage trials were more likely to show a significantly worse result for the experimental than the control arm, and the 2% rate of positive results was less than the expected rate of false positive trials. The point of this analysis was to show that it is difficult to perform any trial in oncology that shows a significant benefit for the new therapy-especially in settings such as advanced disease.…”
mentioning
confidence: 97%